Association of UCP3 (uncoupling protein 3) gene -55C/T polymorphism and obesity in a juvenile population of Iran - Hossein Mohamad Rezaii; Mohsen Kalantari; Sanaz Mahmazi (Fasa University of Medical Sciences, 2018)
Background & Objective: UCP3 is a member of uncoupling proteins which plays an important role in energy homeostasis and it might be important in obesity. C-55T (rs1800849) polymorphism in promoter of UCP3 can affect the expression level of UCP3. The aim of this study was to analyze the association of UCP3 C-55T polymorphism and obesity in a juvenile population of Iran. Material & Methods: peripheral blood sample from 120 obese and 120 normal university students were collected for DNA extraction. Genotyping of C-55T polymorphism in the UCP3 gene was performed by PCR-RFLP method. Chi-square test was applied to analyze the data at P<0.05 significance level. Results: The variant T allele was significantly associated with the obesity risk. The frequency of T allele was 72% in Obese group compared to 40% in normal subjects (P= 0.000, OR=3.8 CI 95% 2.1 - 6.9). Conclusion: The UCP3 C-55T polymorphism was associated with higher BMI and can be regarded as a risk factor for the development of obesity.